Promotion of tourism and available infrastructure facilities in Thanjavur district, Tamil nadu, India - Sangeetha and R. Baskaran, J. Punithavathi*, S. Tamilenthi, T. (Journal of Experimental Sciences, 2011)
Thanjavur district has been choosen for the study. The district predominantly and an agricultural region lies in the eastern part of Cauvery delta. It is the Rice Bowl of Tamil Nadu. It has so many Pilgrimage and historical centre. The big Temple and the other famous temples in the district are known all over the world. Thanjavur was the cultural capital of the country in 1790, Thanjavur gained prominence during the period of Chola Kings, who made it as their capital. Thereafter, it was ruled by Nayaks and Maratta kings who natured art and culture. The cultural, the architectural and the scholarly pursuits of these rulers are reflected in the great monuments like Grand Anaicut, Big Temple and Sarafoji Mahal, library etc., in the district. In this study mainly for infrastructural facilities and other important tourist places are discussed in this study.